Power, influence, and persuasion sell your ideas and make things happen - Luecke, Richard (Boston : Harvard Business School Press, 2005)
Annotation To be effective, managers have to be skilled at acquiring power-and using that power to persuade others to get things done. This guide offers must-know methods for commanding attention, changing minds, and influencing decision makers up and down the organizational ladder.
Annotation.
Title from title screen.
Includes link to companion web site.
Includes bibliographical references and index.
Keywords: Power (Social sciences); Influence (Psychology); Persuasion (Psychology); Influence (Psychology); Persuasion (Psychology); Power (Social sciences); BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books